Vermiremoval of heavy metal in sewage sludge by utilising Lumbricus rubellus - Azizi, A.B.; Lim, M.P.M.; Noor, Z.M.; Abdullah, N. (2013)
Experiments were conducted to remove heavy metals (Cr, Cd, Pb, Cu and Zn) from urban sewage sludge (SS) amended with spent mushroom compost (SMC) using worms, Lumbricus rubellus, for 105 days, after 21 days of pre-composting. Five combinations of SS/SMC treatments were prepared in triplicate along with a control for each treatment in microcosms. Analysis of the earthworms' multiplication and growth and laboratory analysis were conducted during the tenth and fifteenth week of vermicomposting. Our result showed that the final biomass of earthworms (mg) and final number of earthworms showed significant differences between treatments i.e. F=554.70, P=0.00 and F=729.10, P=0.00 respectively. The heavy metals Cr, Cd and Pb contained in vermicompost were lower than initial concentrations, with 90-98.7 percent removal on week ten. However, concentrations of Cu and Zn, that are considered as micronutrients, were higher than initial concentrations, but they were 10-200-fold lower than the EU and USA biosolid compost limits and Malaysian Recommended Site Screening Levels for Contaminated Land (SSLs). An increment of heavy metals were recorded in vermicompost for all treatments on week fifteen compared to week ten, while concentration of heavy metals in earthworms' tissue were lower compared to vermicompost. Hence, it is suggested that earthworms begin to discharge heavy metals into their surroundings and it was evident that the earthworms' heavy metals excretion period was within the interval of ten to fifteen weeks.